Question
upstudy study bank question image url

Given that \( f(x)=(x-6)^{2} \) and \( g(x)=5-3 x \), find (a) \( (f+g)(-1)=\square \) (b) \( (f-g)(-1)=\square \) (c) \( (f g)(-1)=\square \) (d) \( \left(\frac{f}{g}\right)(-1)=\square \) Question Help: Video Submit Question

Ask by Fowler Zimmerman. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

(a) 57 (b) 41 (c) 392 (d) 49⁄8 or 6.125

Solution

Let's evaluate each part step by step using the given functions: \[ f(x) = (x - 6)^2 \] \[ g(x) = 5 - 3x \] We need to find the values of \( f(-1) \) and \( g(-1) \) first. ### Step 1: Calculate \( f(-1) \) and \( g(-1) \) \[ f(-1) = (-1 - 6)^2 = (-7)^2 = 49 \] \[ g(-1) = 5 - 3(-1) = 5 + 3 = 8 \] --- ### (a) \( (f + g)(-1) \) \[ (f + g)(-1) = f(-1) + g(-1) = 49 + 8 = 57 \] **Answer:** \( 57 \) --- ### (b) \( (f - g)(-1) \) \[ (f - g)(-1) = f(-1) - g(-1) = 49 - 8 = 41 \] **Answer:** \( 41 \) --- ### (c) \( (f \cdot g)(-1) \) \[ (f \cdot g)(-1) = f(-1) \times g(-1) = 49 \times 8 = 392 \] **Answer:** \( 392 \) --- ### (d) \( \left(\frac{f}{g}\right)(-1) \) \[ \left(\frac{f}{g}\right)(-1) = \frac{f(-1)}{g(-1)} = \frac{49}{8} = 6.125 \] You can leave the answer as an improper fraction or a decimal, depending on the required format. **Answer:** \( \frac{49}{8} \) or \( 6.125 \) --- ### Summary of Answers - **(a)** \( 57 \) - **(b)** \( 41 \) - **(c)** \( 392 \) - **(d)** \( \frac{49}{8} \) or \( 6.125 \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To find the values of \( (f+g)(-1) \), \( (f-g)(-1) \), \( (fg)(-1) \), and \( \left(\frac{f}{g}\right)(-1) \), we first need to evaluate \( f(-1) \) and \( g(-1) \). 1. Evaluating \( f(-1) \): \[ f(-1) = (-1 - 6)^2 = (-7)^2 = 49 \] 2. Evaluating \( g(-1) \): \[ g(-1) = 5 - 3(-1) = 5 + 3 = 8 \] Now, we can find each expression. (a) \( (f+g)(-1) = f(-1) + g(-1) = 49 + 8 = 57 \) (b) \( (f-g)(-1) = f(-1) - g(-1) = 49 - 8 = 41 \) (c) \( (fg)(-1) = f(-1) \cdot g(-1) = 49 \cdot 8 = 392 \) (d) \( \left(\frac{f}{g}\right)(-1) = \frac{f(-1)}{g(-1)} = \frac{49}{8} \) So the answers are: (a) \( (f+g)(-1) = 57 \) (b) \( (f-g)(-1) = 41 \) (c) \( (fg)(-1) = 392 \) (d) \( \left(\frac{f}{g}\right)(-1) = \frac{49}{8} \)

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy